2022
DOI: 10.1126/sciadv.abf7262
|View full text |Cite
|
Sign up to set email alerts
|

A dominant tubulin mutation causes cerebellar neurodegeneration in a genetic model of tubulinopathy

Abstract: Mutations in tubulins cause distinct neurodevelopmental and degenerative diseases termed “tubulinopathies”; however, little is known about the functional requirements of tubulins or how mutations cause cell-specific pathologies. Here, we identify a mutation in the gene Tubb4a that causes degeneration of cerebellar granule neurons and myelination defects. We show that the neural phenotypes result from a cell type–specific enrichment of a dominant mutant form of Tubb4a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In mouse ependymal cells, for example, which express high levels of Tubb4b and show a tubulin isotype expression pattern similar to ciliated airway cells (Extended data-Fig 3o), centriole amplification and ciliogenesis are nevertheless grossly normal in the absence of TUBB4B. This observation suggests that other isotypes may compensate for the loss of TUBB4B function, including the highly similar TUBB4A (38). These observations are consistent with Drosophila studies suggesting that only isotypes with a particular amino acid sequence in the carboxyl terminus (EGEFXXX) are required for normal axonemal function (1,6,39,40).…”
Section: Discussionmentioning
confidence: 90%
“…In mouse ependymal cells, for example, which express high levels of Tubb4b and show a tubulin isotype expression pattern similar to ciliated airway cells (Extended data-Fig 3o), centriole amplification and ciliogenesis are nevertheless grossly normal in the absence of TUBB4B. This observation suggests that other isotypes may compensate for the loss of TUBB4B function, including the highly similar TUBB4A (38). These observations are consistent with Drosophila studies suggesting that only isotypes with a particular amino acid sequence in the carboxyl terminus (EGEFXXX) are required for normal axonemal function (1,6,39,40).…”
Section: Discussionmentioning
confidence: 90%
“…We next analyzed a Tubb4b knockout to test the role of Tubb4b in cilia, because we previously reported that the Tubb4a knockout mouse was non-phenotypic ( Fertuzinhos et al, 2022 ). We generated Tubb4b knockout mice from EUCOMM embryonic stem (ES) cells, in which the middle two of the four exons in Tubb4b are deleted, resulting in an allele that is likely null and not transcribed, as shown by RT-PCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, 6 of the 23 paralogs of TUBB (Tubulin beta class I) may have been upregulated after TUBB mutation (Figure S1D). Intriguingly, others have experimentally shown that mutations of tubulins can lead to tubulin paralog upregulation in a mouse model of neurodegeneration 29 .…”
Section: Resultsmentioning
confidence: 99%